Diketahui f : R-R
[tex]f(x) = \frac{x + 2}{x - 3} [/tex]
dan g(x)=3x+1. Fungsi (fog)^-1(x) =
[tex]f(x) = \frac{x + 2}{x - 3} [/tex]
dan g(x)=3x+1. Fungsi (fog)^-1(x) =
( f o g )(x) = f[ g(x) ]
= f( 3x + 1 )
[tex] = \frac{(3x + 1) + 2}{(3x + 1) - 3} \\ = \frac{3x + 3}{3x - 2} [/tex]
( f o g )(x) = y
[tex] \frac{3x + 3}{3x - 2} = y[/tex]
3x + 3 = y( 3x - 2 )
3x + 3 = 3yx - 2y
3x - 3yx = -2y - 3
( 3 - 3y ) x = -2y - 3
[tex]x = \frac{ - 2y - 3}{3 - 3y} \\ (fog) {}^{ - 1} (x) = \frac{ - 2x - 3}{3 - 3x} [/tex]
[answer.2.content]